RNA‐Seq analysis and functional characterization revealed lncRNA NONRATT007560.2 regulated cardiomyocytes oxidative stress and apoptosis induced by high glucose. Issue 10 (29th May 2019) - Yu, Manli; Shan, Xinghua; Liu, Yu; Zhu, Jiaqi; Cao, Qingxin; Yang, Fan; Liu, Yang; Wang, Guokun; Zhao, Xianxian
Abstract: Hyperglycemia in diabetic patients would cause cardiomyocytes oxidative stress and apoptosis due to the excessive reactive oxygen species (ROS) accumulation, leading to progressive deterioration of cardiac structure and function. Long noncoding RNAs (lncRNAs) play essential roles on controlling oxidative stress and apoptotic activity. In the present study, RNA sequencing was used to detect the differentially expressed lncRNAs during high glucose‐induced cardiomyocytes oxidative stress and apoptosis. A total of 306/400 lncRNAs were identified as differentially expressed, including 156/198 lncRNAs with increased expression and 150/202 lncRNAs with decreased expression at 24 hours/48 hours after high‐glucose stimulation respectively. Among these dysregulated lncRNAs, 45 lncRNAs were consistently differentially expressed in cardiomyocytes at both two time points after high‐glucose stimulation. Twenty lncRNAs were upregulated and 25 lncRNAs were downregulated at both 24 hours and 48 hours, respectively. The top three upregulated lncRNAs, NONRATT029805.2, NONRATT007560.2, and NONRATT002486.2 were selected for functional studies to determine the role in oxidative stress‐related apoptosis. The results showed that inhibition of non‐ratt007560.2 could abate the formation of ROS and reduce apoptosis, suggesting NONRATT007560.2 might play critical roles in the development of cardiomyopathy. The dysregulated lncRNAs might participate in regulating cardiomyocytes oxidative stress and apoptosis. These findings would be important theoretical and experimental basis for investigation on diabetic cardiomyopathy pathogenesis Abstract : Differential expression profile of long noncoding RNAs (lncRNAs) was identified in cardiomyocytes oxidative stress and apoptosis induced by high glucose. Inhibition of NONRATT007560.2 could abate reactive oxygen species (ROS) formation and reduce apoptosis.